Sustainable hydrogen energy in aviation - A narrative review - Yusaf, Talal F.; Faisal Mahamude, Abu Shadate; Kadirgama, Kumaran; Ramasamy, Devarajan; Farhana, Kaniz; A Dhahad, Hayder Abed; Abd Rahim, Abu Talib (Elsevier Ltd, 2024)
In the modern world, zero-carbon society has become a new buzzword of the era. Many projects have been initiated to develop alternatives not only to the environmental crisis but also to the shortage of fossil fuels. With successful projects in automobile technology, hydrogen fuel is now being tested and utilized as a sustainable green fuel in the aviation sector which will lead to zero carbon emission in the future. From the mid-20th century to the early 21st numerous countries and companies have funded multimillion projects to develop hydrogen-fueled aircraft. Empirical data show positive results for various projects. Consequently, large companies are investing in various innovations undertaken by researchers under their supervision. Over time, the efficiency of hydrogen-fueled aircraft has improved but the lack of refueling stations, large production cost, and consolidated carbon market share have impeded the path of hydrogen fuel being commercialized. In addition, the Unmanned Aerial Vehicle (UAV) is another important element of the Aviation industry, Hydrogen started to be commonly used as an alternative fuel for heavy-duty drones using fuel cell technology. The purpose of this paper is to provide an overview of the chronological development of hydrogen-powered aircraft technology and potential aviation applications for hydrogen and fuel cell technology. Furthermore, the major barriers to widespread adoption of hydrogen technology in aviation are identified, as are future research opportunities.